2007
DOI: 10.2172/919780
|View full text |Cite
|
Sign up to set email alerts
|

Final Report - Novel Approach to Non-Precious Metal Catalysts

Abstract: This project was directed at reducing the dependence of PEM fuel cell catalysts on precious metals. The primary motivation was to reduce the cost of the fuel cell stack as well as the overall system cost without loss of performance or durability. Platinum is currently the catalyst of choice for both the anode and the cathode. However, the oxygen reduction reaction (ORR) which takes place on the cathode is an inherently slower reaction compared to the hydrogen oxidation reaction (HOR) which takes place on the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…Our short study on stability of the prepared materials in humid atmospheres showed that in most cases the materials were not stable if exposed to the flow of humidified air at RH = 90% and temperatures between 25 • C and 70 • C. The materials mostly decomposed into BaCO 3 and In(OH) 3 . Under a lower humidification of RH = 50% only BIO decomposed, while the other compositions showed higher stability at all temperatures.…”
Section: Structure and Stabilitymentioning
confidence: 96%
See 3 more Smart Citations
“…Our short study on stability of the prepared materials in humid atmospheres showed that in most cases the materials were not stable if exposed to the flow of humidified air at RH = 90% and temperatures between 25 • C and 70 • C. The materials mostly decomposed into BaCO 3 and In(OH) 3 . Under a lower humidification of RH = 50% only BIO decomposed, while the other compositions showed higher stability at all temperatures.…”
Section: Structure and Stabilitymentioning
confidence: 96%
“…In recent years, more intense research has taken place to develop intermediate temperature fuel cells (100-500 • C) since they combine the advantages of both high and low temperature fuel cells [1][2][3][4][5][6][7][8]. One of the major approaches to achieve this goal involves searching for new electrolyte materials with a sufficiently high ionic conductivity in that temperature range.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Non-precious metal catalysts have been proposed for the replacement of platinum in low temperature fuel cells, however the low mass activity and low stability have prevented them from being successfully implemented [1][2][3]. The use of highly dispersed platinum crystallites on high surface area carbon can increase the active surface area and electrocatalytic activity of the catalysts, thereby reducing the Pt loadings in the cell.…”
Section: Introductionmentioning
confidence: 99%